Breast MRI phenotype and background parenchymal enhancement may predict tumor response to neoadjuvant endocrine therapy. Issue 6 (31st July 2018) - Hilal, Talal; Covington, Matthew; Kosiorek, Heidi E.; Zwart, Christine; Ocal, Idris T.; Pockaj, Barbara A.; Northfelt, Donald W.; Patel, Bhavika K.
Abstract: Neoadjuvant endocrine therapy (NET) is increasingly used for the treatment of estrogen receptor positive, HER2 negative breast cancer. We evaluated whether MRI phenotype and background parenchymal enhancement (BPE) can predict response to NET. Patients with localized breast cancer treated with NET and had a pre‐treatment breast MRI were identified. Baseline MRI phenotype and BPE was interpreted by a single radiologist blinded to the results of systemic therapy. Response was defined as stable disease or reduction in tumor size on clinical and/or ultrasound examination. Of the 21 patients identified, 17 were responders; all patients with minimal/mild BPE had a response compared to 5/9 (56%) patients with moderate/marked BPE ( P  = 0.02). All four nonresponders had moderate/marked BPE as compared to 5/17 (29%) responders ( P  = 0.02). This pilot study suggests that minimal/mild BPE may be predictive of a positive response to NET. A higher degree of background enhancement was significantly predictive of negative response to NET.